Musical meaning : toward a critical history - Kramer, Lawrence, 1946- (University of California Press, 2002)
Lawrence Kramer has been a pivotal figure in the development of the controversial new musicology, integrating the study of music with social and cultural issues. This book continues and deepens the trajectory of Kramer's thinking as it argues that humanistic meaning is a basic force in music history.